ORGANIZACIÓN DE LA CONTABILIDAD EN EL “TALLER J.G” DE LA CIUDAD DE LOJA. PERÍODO DEL 01 DE SEPTIEMBRE AL 31 DE DICIEMBRE DEL 2017 - Rengel Ramírez, Jordy Javier (2018)
The thesis entitled ORGANIZATION OF ACCOUNTING IN THE "WORKSHOP J.G" OF THE CITY OF LOJA. PERIOD FROM 01 SEPTEMBER TO DECEMBER 31, 2017, is mainly oriented to propose an accounting organization in the company, which allows its owner to know the real economic-financial situation of the same, reflected through the Financial Statements. It is also an essential requirement for obtaining the Bachelor's and Bachelor's Degree in Accounting and Auditing, Auditing Public Accountant according to the Rules of Academic Regulations of the Universidad Nacional de Loja. The development of the thesis was carried out through the application of several research methods, the same ones that were used in the application of the set of principles and rules during the theoretical-practical development; in the study of the norms, codes and laws necessary for the construction of the bibliographic review; in the classification and registration of activities carried out in the company; in carrying out the analysis of the daily operations of the "Taller J.G", with which it was possible to prepare the plan and manual of accounts, as well as assistants for the registration of the transactions in the accounting books; in the summary of the research work, which allowed elaborating and substantiating the conclusions and recommendations raised to the owner of the company, and for the different calculations of each one of the phases of the accounting process. 6 The fulfillment of objectives was carried out gradually with the development of the thesis, in such a way that the first objective was fulfilled since it began with the preparation of a chart of accounts adjusted to the need and nature of the workshop, based on the which was designed a manual of accounts where the description, movement and respective balance of each one of the patrimonial accounts and of results, which were used later in the development of the accounting process. Subsequently, the initial inventory of goods, rights and obligations that the company had at the beginning of its operations was carried out. Which determined that the company had the following values: in assets $ 198,517.20 in liabilities $ 636.36 and equity $ 197,880.84. Then the main and secondary registers were designed in compliance with the third objective, for which purchase records, accounts receivable, payment roles and social provisions were prepared, which allowed synthesizing the information of the transactions carried out by the company through a single accounting entry in the journal. Then, the fourth objective was met, which is the chronological and orderly record of the transactions carried out by the company in each of the phases that make up the accounting process until obtaining the Financial Statements, obtaining in the Income Statement the following values: income $ 43,605.00 expenses $ 14,313.43 and profit for the year $ 29,291.57 7 The Statement of Financial Position that presents in assets $ 228.308,20 in liabilities $ 7.631,27 and in equity $ 220,676.93. The cash flow statement that in operating activities has a value of $ 68.300,53 while in the investment and financing activities there was no movement of cash during the period. Finally, the respective conclusions and recommendations are presented according to the existing needs of the company, so that the owner-manager considers them as an option in taking corrective measures that contribute to the achievement of business goals and objectives. The aforementioned conclusions emphasize the development of the accounting process with adherence to the Tax Rules starting from the Initial Inventory until obtaining the Financial Statements where its results showed that the company during the period from September 1 to December 31 of the 2017 obtained a Net Profit of $ 22,796.09, therefore, it is necessary to recommend that the accounting process developed in this thesis work continue to be applied in order to facilitate the recording of the economic operations carried out by the company, and to know the situation economic-financial of the same in a determined period.